2010
DOI: 10.1002/cbic.200900665
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Liposidomycin‐like A‐90289 Antibiotics Featuring a New Type of Sulfotransferase

Abstract: Lip reading: The biosynthetic gene cluster for A‐90289, a fatty acid nucleoside antibiotic, was cloned and sequenced. The sulfotransferase LipB is demonstrated to be essential for A‐90289 biosynthesis, and in vitro characterization revealed LipB utilizes p‐nitrophenylsulfate as an aryl sulfate donor and a variety of nonaryl acceptors including caprazamycin A to give the 2′‐O‐sulfated product, A‐90289A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…2) (29,30). Additional members of the GlyU-containing nucleoside antibiotics with identified biosynthetic gene clusters include liposidomycins (31), caprazamycins (32), muraymycin (33), muraminomicin (34), and the recently discovered sphaerimicins (35).…”
Section: Capuramycin-type Antibiotics Include A-500359s Frommentioning
confidence: 99%
“…2) (29,30). Additional members of the GlyU-containing nucleoside antibiotics with identified biosynthetic gene clusters include liposidomycins (31), caprazamycins (32), muraymycin (33), muraminomicin (34), and the recently discovered sphaerimicins (35).…”
Section: Capuramycin-type Antibiotics Include A-500359s Frommentioning
confidence: 99%
“…[13] Structureactivity studies with synthesised peptidyl nucleoside analogues revealed that the terminal amino group, the N-methyl-Daba and probably the uridine moiety are most important for the inhibition of translocase I. [14,15] Recently, the identification and analysis of the gene clusters for caprazamycins, [16,17] liposidomycins [18][19][20] and capuramycintype A-500359 [21] has given the first insights into the biosynthesis of the structurally unusual nucleoside antibiotics that target translocase I. However, little is known about the formation of the uridylpeptide-type translocase I inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis gene clusters for a number of pyrimidine nucleoside antibiotics have been elucidated, including nikkomycin (4,46), polyoxin (8), blasticidin S (13), A-500359s and A-503803s (25), caprazamycin (38), lipisidomycin (39) and its analogue A-90289 (24), pacidamycins (50,60), muraymycin (12), and tunicamycin (9). However, biosynthesis studies for the amicetin group of disaccharide nucleoside antibiotics are not yet available.…”
mentioning
confidence: 99%